Transitioning to Renewwable Energy: Challenges, Policies, and Economic Implications in Indonesia (1990-2023) - Hidayat , Muhammad Syahrul; Hamid, Ahmad Munir; Mazidah , Nurul (OECONOMICUS Journal of Economics, 2025)
The Indonesian Government, through the National Energy Council, has set a roadmap for achieving zero emissions energy by 2060, with targets for increasing renewable energy use each year. Despite aiming for a 23% target by 2025, the current annual increase in new renewable energy in Indonesia is only 0.55%, far below the required 0.9%. This calls for more progressive policy planning to achieve the new energy target. Challenges include the dispersed nature of Indonesia's renewable energy potential, limited grid capacity, and domestic industry capability. This study examines the impact of renewable and non-renewable energy on Indonesia's economic growth from 1990 to 2023. Employing a quantitative approach with the Error Correction Model (ECM) statistical test, the research explores short-term and long-term relationships among variables. Findings reveal that non-renewable energy consumption (CONRE) positively and significantly impacts economic growth by 6.15%, while renewable energy for electricity (REFE) also has a positive and significant effect of 7.19%. However, renewable energy from water resources (REWR) shows no significant positive impact in the long term, at only 0.19%. In the short term, CONRE positively and significantly affects economic growth by 6.43%, whereas REFE and REWR exhibit insignificant impacts of 0.075% and 0.071% respectively. The study suggests the government should optimize renewable energy potential to achieve more environmentally friendly energy policies, considering factors beyond those studied, such as societal innovation and creativity in identifying energy source potential and gaps.